2011
DOI: 10.1186/1479-5876-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of the human sodium iodide symporter to facilitate deep tissue imaging does not alter oncolytic or replication capability of a novel vaccinia virus

Abstract: IntroductionOncolytic viruses show promise for treating cancer. However, to assess therapeutic efficacy and potential toxicity, a noninvasive imaging modality is needed. This study aimed to determine if insertion of the human sodium iodide symporter (hNIS) cDNA as a marker for non-invasive imaging of virotherapy alters the replication and oncolytic capability of a novel vaccinia virus, GLV-1h153.MethodsGLV-1h153 was modified from parental vaccinia virus GLV-1h68 to carry hNIS via homologous recombination. GLV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 28 publications
1
60
0
1
Order By: Relevance
“…It should be taken into account in this regard, however, that at the viral doses used (5×10 6 pfu), both the control and the enzyme-expressing virus were already highly effective in inhibiting tumor growth: as exemplified by Fig. 6B-D, even in the absence of DOX-or pg-micelle-cotreatment, tumor volumes never exceeded 200%, confirming the strong oncolytic potential of vaccinia viruses [21][22][23][24][25][26][27] . Interestingly, when combined with free DOX, the oncolytic activity of GLV-1h190 was somewhat reduced (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be taken into account in this regard, however, that at the viral doses used (5×10 6 pfu), both the control and the enzyme-expressing virus were already highly effective in inhibiting tumor growth: as exemplified by Fig. 6B-D, even in the absence of DOX-or pg-micelle-cotreatment, tumor volumes never exceeded 200%, confirming the strong oncolytic potential of vaccinia viruses [21][22][23][24][25][26][27] . Interestingly, when combined with free DOX, the oncolytic activity of GLV-1h190 was somewhat reduced (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a number of studies, it was shown that recombinant vaccinia viruses (rVACV) derived from the Lister-strain are effective in treating different solid tumor types (reviewed in 21 ). Monitoring of the successful tumor colonization and the therapeutic effects can be performed by different imaging modalities, including optical 24 , optoacoustic 25 , PET- 26,27 , and by MR-imaging 25 . Reporter gene-encoding rVACV can therefore be considered theranostic agents [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…All mice (n = 6 per group) treated with intrapleural injection of 1×10 4 or 1×10 5 PFUs of GLV-1h153 were alive 1 month after tumor establishment. Mean survival in untreated controls was 21 days and all mice had expired by day 29.…”
Section: Intrapleural Treatment With Glv-1h153 Results In Improved 30mentioning
confidence: 99%
“…Treatment with 1×10 5 PFUs of GLV-1h153 resulted in a progressive and significant reduction in tumor burden for the duration of the survival study. By 3 weeks after randomization, mice treated with 1×10 5 PFUs of GLV-1h153 demonstrated a nearly 3-log decrease in average bioluminescent radiance relative to controls (p<0.001).…”
Section: Intrapleural Treatment With Glv-1h153 Reduces Tumor Burden Imentioning
confidence: 99%
See 1 more Smart Citation